Eighth grade students' attitude, anxiety, and achievement pertaining to mathematics lessons - Yaratan, Huseyin; Kasapoglu, Leman (Elsevier Science Bv, 2012)
The aim of this study is to investigate differences in attitudes, anxiety, and mathematical achievement due to gender, and school location; and to depict how well anxiety and attitudes towards mathematics determine students' mathematical achievement controlling for gender and school location. Attitude and anxiety scales were administered to 188 eighth grade students and the data collected were analyzed using t-test and multiple regression analyses. Results revealed significant differences in attitude, and in mathematics scores, but no significant differences in the anxiety scores with respect to gender, and location of schools. R-2=.448 implied that 44.8% of the variability in the mathematical achievement of students can be explained by students' anxiety (Beta=-.432), attitudes (Beta=.216), gender (Beta=-.113), and school location (Beta=-.291). R-2 change=.377, depicts that students from similar school locations and with the same gender are likely to have higher achievement scores in mathematics if they have higher positive attitudes and lower anxiety.
4th World Conference on Educational Sciences (WCES) -- FEB 02-05, 2012 -- Univ Barcelona, Barcelona, SPAIN
Keywords: mathematics anxiety; attitude towards mathematics; achievement in mathematics; gender; school location